Governance and Public Policy Challenges in Industrial Downstreaming: The Case of Indonesia’s Nickel Sector - Sarjito, Aris (Jejaring Administrasi Publik, 2025)
This study examines the effectiveness of Indonesia’s industrial downstreaming policy, with a particular focus on the nickel sector, as a strategic effort to shift the economy from raw material exports to domestic value-added processing. Using a qualitative approach with secondary data sources, including government documents, policy reports, and scholarly literature, the study investigates institutional bottlenecks and patterns of bureaucratic interaction. Findings reveal that while the downstreaming policy has successfully attracted foreign investment and stimulated industrial growth in key sectors like nickel refining and EV supply chains, its long-term sustainability is hindered by regulatory unpredictability, prolonged licensing processes, and fragmented coordination between national and regional authorities. Additionally, trade tensions such as WTO-related disputes exacerbate institutional pressure. The study concludes that to enhance the success of downstreaming, Indonesia must implement coherent regulations, streamline its bureaucratic mechanisms, and strengthen multilevel governance. Embracing digital governance, fostering transparency, and providing targeted investment incentives are critical to ensuring policy effectiveness and reinforcing Indonesia’s position in global value-added production networks. Keywords: economic policy; industrial downstreaming; investment incentives; public sector governance; regulatory reform